Takaful Advancements: Governance, Products, Post COVID-19, Sustainability and Takatech - Issa Khan, (2025)
This book covers the governance and regulatory requirements of takaful companies, including the Shariah Governance Structure in different countries. It also discusses challenges facing takaful companies and provides possible solutions. The book offers a detailed description of takaful products and services, as well as suggestions for developing new ones in response to the contemporary business environment. Additionally, it examines the post-COVID-19 impacts on takaful companies worldwide and proposes ways toovercome these challenges. It delves into crucial issues regarding the sustainability of takaful, including financial, social, environmental, operational and ethical aspects. It also explores ways to improve the industry’s sustainability through advanced technology. The book emphasises environmental concerns for takaful companies and discusses International Financial Reporting Standards in accounting for the takaful system as well as enterprise risk management to navigate industry challenges. Additionally, it covers the importance of Insurtech and Takatech, recommending increased adoption of Takatech in the Takaful industry.